Validating the kinesthetic play model: A quantitative study on enhancing early mathematical skills in Indonesian preschoolers - Utoyo, Setiyo; Ismaniar, Ismaniar; Hazizah, Nur; Handrianto, Ciptro (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the effectiveness of the Kinesthetic Play Model in enhancing early mathematical skills among elementary school children in Padang, West Sumatra, Indonesia. The research aims to examine the relationship between kinesthetic play and mathematical performance, focusing on the role of engagement and interactive learning strategies. A sample of 933 participants was surveyed using a quantitative research design, and structural equation modeling (SEM) was employed for data analysis. Results showed a significant positive correlation between kinesthetic play and improvements in mathematical skills (β = 0.45, p < 0.01). Furthermore, the model revealed that children who participated in kinesthetic activities demonstrated a 38% higher achievement rate in problem-solving tasks compared to those who did not. The analysis also indicated that engagement in kinesthetic learning experiences was a strong predictor of higher performance in basic mathematical operations, with a standardized coefficient of 0.67. These findings support the theoretical framework of active learning and provide empirical evidence for integrating kinesthetic play into early education to foster mathematical development. This study contributes to the growing body of literature on interactive learning strategies and presents practical implications for educators aiming to improve children's engagement and academic outcomes in mathematics.